2008
DOI: 10.1093/pasj/60.sp1.s351
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Evolution of GRB060904A Observed with Swift and Suzaku- Possibility of Inefficient Electron Acceleration

Abstract: We observed an X-ray afterglow of GRB 060904A with the Swift and Suzaku 1 satellites. We found rapid spectral softening during both the prompt tail phase and the decline phase of an X-ray flare in the BAT and XRT data. The observed spectra were fit by power-law photon indices which rapidly changed from Γ = 1.51 +0.04 −0.03 to Γ = 5.30 +0.69 −0.59 within a few hundred seconds in the prompt tail. This is one of the steepest X-ray spectra ever observed, making it quite difficult to explain by simple electron acce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Therefore, because of the analogies between long and short GRBs, the EXP model may be appropriate to describe the time behaviour of rapid decay in SGRBs. Yonetoku et al (2008) and Moretti et al (2008) reported similar rapid decline in time with strong spectral evolution in long GRBs. Especially Yonetoku et al (2008) interpreted the temporal and spectral behavior as dynamic evolution of a spectral model, i.e., a spectral model of a broken power-law with an exponential cutoff moves through the observational energy window of XRT during the rapid decay phase.…”
Section: Exponential Decay In Early Phasementioning
confidence: 63%
See 1 more Smart Citation
“…Therefore, because of the analogies between long and short GRBs, the EXP model may be appropriate to describe the time behaviour of rapid decay in SGRBs. Yonetoku et al (2008) and Moretti et al (2008) reported similar rapid decline in time with strong spectral evolution in long GRBs. Especially Yonetoku et al (2008) interpreted the temporal and spectral behavior as dynamic evolution of a spectral model, i.e., a spectral model of a broken power-law with an exponential cutoff moves through the observational energy window of XRT during the rapid decay phase.…”
Section: Exponential Decay In Early Phasementioning
confidence: 63%
“…Yonetoku et al (2008) and Moretti et al (2008) reported similar rapid decline in time with strong spectral evolution in long GRBs. Especially Yonetoku et al (2008) interpreted the temporal and spectral behavior as dynamic evolution of a spectral model, i.e., a spectral model of a broken power-law with an exponential cutoff moves through the observational energy window of XRT during the rapid decay phase. Here the physical interpretation of the break energy and the cutoff energy is the E peak corresponding to the minimum energy of accelerated electrons and the synchrotron cutoff, respectively.…”
Section: Exponential Decay In Early Phasementioning
confidence: 63%
“…A possible thermal component has also been tried. However, Yonetoku et al (2008) showed that introducing a thermal component is not sufficient to explain all of the spectral softening, and thus additional spectral evolution is required. In investigating the origins for the spectral evolution of GRB 070616, Starling et al (2008) ruled out the possibility that a superposition of two power-laws causes the evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Many careful analyses revealed that there do exist some bursts with their peak energy E peak decreasing from a higher band to a much lower band. These bursts include: GRB 060124, from 108 keV to 1.3 keV (Butler & Kocevski 2007); GRB 060614, from 8.6 keV to 1.1 keV (Butler & Kocevski 2007;Mangano et al 2007); GRB 060904A, from 163 keV to 2.28 keV (Yonetoku et al 2008); GRB 061121, from 270 keV to 0.95 keV (Butler & Kocevski 2007); GRB 070616, from 135 keV to ∼4 keV (Starling et al 2008). For GRB 070616, the spectral softening evolution was observed even in the prompt emission phase: its duration is T 90 = 402.4s, while the softening starts from 285s and extends to 1200s (Starling et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…where Γ = β + 1 is the power law photon index, and k is a parameter to define the sharpness of the high energy cutoff in the spectrum, E c (t) is the time-dependent characteristic photon energy, and N 0 (t) is a time-dependent photon flux (in units of photons · keV −1 cm −2 s −1 ) at 1 keV (Arnaud 1996). The choice of this function was encouraged by the fact that the spectral evolution of some GRB tails can be fitted by such an empirical model (Campana et al 2006;ZLZ07;Yonetoku et al 2008). According to Eqs.…”
Section: Data Reduction and Simulation Methodsmentioning
confidence: 99%